Recent Advances in Metabolically Engineered Microorganisms for the Production of Aromatic Chemicals Derived From Aromatic Amino Acids - Shen, Yu-Ping; Niu, Fu-Xing; Yan, Zhi-Bo; Fong, Lai San; Huang, Yuan-Bin; Liu, Jian-Zhong (Frontiers in Bioengineering and Biotechnology, 2020)
Aromatic compounds derived from aromatic amino acids are an important class of diverse chemicals with a wide range of industrial and commercial applications. They are currently produced via petrochemical processes, which are not sustainable and eco-friendly. In the past decades, significant progress has been made in the construction of microbial cell factories capable of effectively converting renewable carbon sources into value-added aromatics. Here, we systematically and comprehensively review the recent advancements in metabolic engineering and synthetic biology in the microbial production of aromatic amino acid derivatives, stilbenes, and benzylisoquinoline alkaloids. The future outlook concerning the engineering of microbial cell factories for the production of aromatic compounds is also discussed.